A EDUCAÇÃO AMBIENTAL NO CONTEXTO DA FORMAÇÃO DO AGENTE SOCIAL DA TERCEIRA IDADE COMO EDUCADOR - Caparrós, Ricardo Pasin (2006)
The concept of aging as a decline of human existence loses its meaning in contemporary societies as the idea of the Third Age takes hold. In this context, the Vergueiro Campus of the Universidade Metodista de São Paulo in São Bernardo do Campo offers a course entitled Universidade Livre da Terceira Idade The purpose of this course is to graduate social agents. One of the objectives of this course is environmental education. In this paper, environmental education is defined as that which surrounds the individual: it includes the natural, the man-made, the social/cultural and the corresponding institutions, knowledge and values. Therefore, the environmental educator will study and understand environmental questions and will be able to interact with people in various contexts. However, the social agent of the Third Age will use the necessary attributes required as an environmental educator. He will utilize the environmental knowledge needed for intervention actions. He will also optimize his personal development. The objective of this paper is to analyze the environmental perception of the university students of the Third Age at the beginning of the course. This will be within the environmental education module. This paper will also verify if the contents and methodology utilized in the environmental education discipline contribute not only to the development of the social agent of the Third Age but also to his performance as an environmental educator. The theory of this paper was based on the complexity concept of Edgar Morin, the environmental ideas of Enrique Leff, the educational concepts of Paulo Freire and the understanding of environmental education of Marcos Reigota. Analytical techniques of documents, questionnaires and focus groups were used as part of the methodology. The data collected suggest the viability of Third Age individuals as environmental educators in intervention actions in their local areas.